Interiors of the Mandapa of the Suswani Mata Temple - Temples of India Project Team (Jio Institute, 2024)
View of the interiors of the mandapa (pillared hall) of the Suswani Mata Temple. Though the exteriors of the entire mandapa are renovated, the interiors are survived with four pillars which form part of the original plan of the temple. These four pillars are in front of the garbhagriha (sanctum sanctorum) entrance of the temple. The mandapa is also linked to the exterior of the mulaprasada (main shrine). One can see the pradakshina path (circumambulatory path) that runs along the garbhagriha.